Analisis Dosis Perekat Tepung Biji Nangka Terhadap Karakteristik Mutu Briket Arang Campuran Kulit Kacang Tanah Dan Sekam padi - Aura Salsabila Evendi (Fakultas Teknologi Pertanian, 2026)
The utilization of biomass waste as an alternative energy source is an important strategy to reduce dependence on fossil fuels and support sustainable energy development. Peanut shells and rice husks are agricultural residues with potential to be converted into charcoal briquettes due to their high carbon content. This study aimed to analyze the effect of different dosages of jackfruit seed flour adhesive on the quality characteristics of charcoal briquettes made from peanut shells and rice husks. The experiment employed three replications and three levels of adhesive concentration: 5%, 7%, and 10%. The observed parameters were moisture content, ash content, calorific value, combustion duration, and combustion temperature. Data were analyzed using one-way Analysis of Variance (ANOVA) followed by Tukey’s Honestly Significant Difference (HSD) test at a 5% significance level. The results showed that adhesive dosage significantly affected all tested characteristics. Moisture content increased from 4.5% to 5.8%, while ash content decreased from 16.5% to 13.2% with increasing adhesive concentration. The highest calorific value was obtained at the 10% adhesive dosage, reaching 5,355 cal/g, exceeding the Indonesian National Standard (SNI) minimum requirement of 5,000 cal/g. This treatment also produced the longest combustion duration and the highest combustion temperature. Overall, the 10% adhesive concentration yielded the best briquette quality, indicating the potential of jackfruit seed flour as a natural binder for biomass briquette production.
Validasi dan Finalisasi Ratna 24 Juli 2026
Keywords: Analisis Dosis Perekat Briket